Selecting phosphorus-solubilizing strains of purple nonsulfur bacteria isolated from pineapple cultivated acid sulfate soils - Huu, Tran Ngoc; Thu, Ha Ngoc; Anh, Nguyen Huynh Minh; Trong, Nguyen Duc; Nhan, Tran Chi; Thu, Le Thi My; Xuan, Ly Ngoc Thanh; Quang, Le Thanh; Khuong, Nguyen Quoc (Penerbit Universiti Kebangsaan Malaysia, 2024)
The presence of acid sulfate soils is such an obstacle for pineapple cultivation in Vietnam due to their low pH, high toxicity and poor nutrient availability, especially phosphorus (P), which is immobilized by cations in the soils. Therefore, the study occurred to select purple nonsulfur bacteria (PNSB) strains that can solubilize P under toxic and acidic conditions. There were 33 strains that can tolerate the acidic condition, and they were selected and tested for viability and P solubilization under conditions containing Al3+, Fe2+, and Mn2+ toxins. Four strains, including W15, W39, W42 and W48 suffered from growth inhibition by Al3+, Fe2+ and Mn2+ less than the other strains under both microaerobic light and aerobic dark conditions (ML and AD conditions). In addition, there were four strains (W15, W25, W42 and W48) solubilizing Al-P well (21.4-25.2 mg L-1), two strains (W23 and W42) solubilizing Fe-P well (15.9-17.3 mg L-1), and two strains (W17 and W42) solubilizing Ca-P well (23.0-36.4 mg L-1) under both ML and AD conditions. Ultimately, there were five strains selected (W17, W23, W25, W42 and W48) and identified as Rhodopseudomonas palustris strain W17 and W23, Cereibacter sphaeroides strain W23, W42 and W48 based on the 16S rRNA technique. The selected strains also produced ALA, EPS and siderophores at 1.31-2.19 mg L-1, 0.78-1.89 mg L-1, and 16.2-55.6%, respectively. Therefore, these strains were promising in providing nutrients for pineapples in the form of biofertilizer.